Analisis Model Sambungan Baut Baja M12 Terhadap Kekuatan Tarik Material Plat ST-42 - Muh Rifky Algifari; Ratnawati; Anoi, Yano Hurung (Jurnal Teknik Juara Aktif Global Optimis, 2023)
Abstract Along with the increasingly rapid development of tecnology of technology in science today, it will have a very complex impact on companies which are required to produce quality product in accordance with market demand, especially in the development of technology in the fields of construction, automotive, manufacturing and home industry. Comparing the 2 bolt, 3 bolt connection on the tensile strength of ST steel plate plate material. 42 To determine the magnitude of the greater the tensile strength of ST steel plate material.42 To Determine the magnitude of the influence of variations in connection models of 2 bolts, 3 bolts as an effort to increasear the tensile strength of ST steel plate material. 42 To determine the magnitude of the influence of variations in connection models of 2 bolts, 3 bolts as an effort to increase the tensile strength of ST 42 plate material. The more bolts you use in a connection, the greater the tensile strength production. Namely, for the connection, 2 vertical model bolts with a strength value of max = 96.019 Mpa, 3 horizontal model bolts with a strength value of max = 175.556 Mpa, Parallelogram style bolts (a) are the best type of connection as a result of tensile test. Variations in bolt connection models influence efforts to increase tensile strength for both the 2 bolt, 3 bolt models, namely for the 2 bolt connection the horizontal model max 2 bolt = 89.722 Mpa, the vertical model max 2 bolt = 96.019 Mpa and the incline model max 2bolt = 86,667 Mpa and for a connection of 3 bolts, horizontal model max 3 bolt = 137,222 Mpa, vertical model max 3 bolt = 120,556 Mpa , inclined model max 3 bolt = 122,315 Mpa , triangular model (a) max 3 baut = 134,074 Mpa and triangular model (b) max 3 baut = 133,889 Mpa. Keywords: Bolted Connection, ST 42 Steel